Diastolic dysfunction in controlled hypertensive patients with mild–moderate obstructive sleep apnea. (6th May 2015) - Lisi, Elisabetta; Faini, Andrea; Bilo, Grzegorz; Lonati, Laura Maria; Revera, Miriam; Salerno, Sabrina; Giuli, Valentina; Lombardi, Carolina; Parati, Gianfranco
Abstract: Background: Hypertension and severe obstructive sleep apnea (OSA) may independently contribute to left ventricular diastolic dysfunction. However, scanty data is available on this issue in hypertensives with mild–moderate OSA. Methods and results: We performed polysomnography, echocardiography and 24 h ambulatory blood pressure monitoring in 115 treated essential hypertensives with suspicion of OSA. After exclusion of severe/treated OSA and/or cardiovascular disease patients, mild–moderate OSA (5 ≤ apnoea/hypopnoea index < 30 events·h − 1 ) was diagnosed in 47.3% of the remaining 91 patients, while 52.7% were free of OSA. Transmitral early (E) and late (A) peak flow velocities were assessed in 69 patients, and mitral annular velocity (E′) in 53. Compared to non-OSA, mild–moderate OSA heart rate was higher (p = 0.031) while E/A was lower (p < 0.001) without differences in 24 h mean systolic and diastolic blood pressures (125.36 ± 12.46/76.46 ± 6.97 vs 128.63 ± 11.50/77.70 ± 7.72 mm Hg, respectively, NS). Patients with E′ < 10 cm/s and E/A < 0.8 showed a lower mean SpO2 than subjects with normal diastolic function (p = 0.004; p < 0.001). In a logistic regression model age, mean SpO2, daytime heart rate and nocturnal diastolic blood pressure fall were associated with altered relaxation pattern, independently from BMI and gender. Conclusions: In controlled hypertensives mild–moderate OSA may be associated with early diastolic dysfunction, independently from age, gender and mean blood pressure and in the absence of concentric left ventricular hypertrophy. Moreover nocturnal hypoxia may be a key factor in determining early diastolic dysfunction, under the synergic effects of hypertension and mild–moderate OSA.